INFLUENCE OF MATERIALS DISPERSION ON SPEEDS OF THE SOLID-PHASE RESTORATION PROCESSES - S. L. Rovin (Литьë и металлургия, 2014)
At recovery of metal discard the scale factor influences intensity of realization of oxidation-reduction reactions. Carrying out of recycling in dynamic layers of disperse materials accelerates significantly the process of solid-phase restoration in comparison with recovery of lump components.